A System for Uncovering Latent Connectivity of Health Care Providers in Online Reviews - Bäumer, Frederik Simon; Geierhos, Michaela; Schulze, Sabine (Information and Software Technologies. 21st International Conference, ICIST 2015, Druskininkai, Lithuania, October 15-16, 2015. Proceedings)
The contacts a health care provider (HCP), like a physician, has to other HCPs is perceived as a quality characteristic by patients. So far, only the German physician rating website jameda.de gives information about the interconnectedness of HCPs in business networks. However, this network has to be maintained manually and is thus incomplete. We therefore developed a system for uncovering latent connectivity of HCPs in online reviews to provide users with more valuable information about their HCPs. The overall goal of this approach is to extend already existing business networks of HCPs by integrating connections that are newly discovered by our system. Our most recent evaluation results are promising: 70.8 % of the connections extracted from the reviews texts were correctly identified and in total 3,788 relations were recognized that have not been displayed in jameda.de’s network before.
Keywords: Latent Connectivity; Person Named Entity Recognition and Disambiguation; Health Care Provider Reviews

Understanding the Patient 2.0: Gaining Insight into Patients' Rating Behavior by User-generated Physician Review Mining - Geierhos, Michaela; Bäumer, Frederik Simon; Schulze, Sabine; Klotz, Caterina (Modeling and Using Context. 9th International and Interdisciplinary Conference, CONTEXT 2015, Lanarca, Cyprus, November 2-6, 2015. Proceedings)
Patients 2.0 increasingly inform themselves about the quality of medical services on physician rating websites. However, little is known about whether the reviews and ratings on these websites truly reflect the quality of services or whether the ratings on these websites are rather influenced by patients’ individual rating behavior. Therefore, we investigate more than 790,000 physician reviews on Germany’s most used physician rating website jameda.de. Our results show that patients’ ratings do not only reflect treatment quality but are also influenced by treatment quality independent factors like age and complaint behavior. Hence, we provide evidence that users should be well aware of user specific rating distortions when intending to make their physician choice based on these ratings.
Keywords: Health 2.0; Rating Behavior; Patient Opinion Mining on Physician Rating Websites

Kinderstärken – Kinder stärken. Erziehung und Bildung ressourcenorientiert gestalten

Das Haus als Exponat und sein Stellenwert für die Forschungs- und Vermittlungsarbeit im Freilichtmuseum (dt. u. engl.) - Seng, Eva- Maria (Conference Report/Tagungsbericht der 26. Konferenz des Verbandes Europäischer Freilichtmuseen August 2013)

August Grisebach und die Neuausrichtung der deutschen Kunstgeschichte Anfang des 20. Jahrhunderts - Seng, Eva- Maria (Die Universität Breslau in der europäischen Kultur des 19. und 20. Jahrhunderts, in: Wroclaw University in the European Culture of 19th and 20th Centuries. Papers from the International Scientific Conference, Wroclaw 2011)

Auf Stroh sitzend studieren. Zur Geschichte des Hochschulbaus - Seng, Eva- Maria (Forschung & Lehre)

The situation of German Heritage during the Past Forty Years - Seng, Eva- Maria (patrimoine et architecture. Matériel/Immatériel 40 ans de patrimoine, 1970-2010, Cahier 21-22, Avril 2015, Office du patrimoine et des sites, Département de l’aménagement, du logement et de l’énergie)

Patrimoine - global - régional - glocal. Patrimoine matériel et immatériel – une alternative? - Seng, Eva- Maria (Du le Cahiers n3, Le patrimoine culturel immatériel. Regards croisés de France et d’Allemagne, Paris)

Kirchenbauten und konfessionelle Konflikte in bikonfessionellen Städten und Orten in der Frühen Neuzeit – Simultaneen - Seng, Eva- Maria (Protestantischer Kirchenbau in der Frühen Neuzeit in Europa. Grundlagen und neue Forschungskonzepte. Protestant Church Architecture in Early Modern Europe. Fundamentals and New Research Approaches)

Das deutsche Drama im Überblick - Eke, Norbert Otto

Auswirkungen der Arbeitswelt auf Leben, Wohnen, Städtebau - Seng, Eva- Maria (Arbeit – Dimensionen eines gesamtgesellschaftlichen Phänomens)
demnächst in: Politica et Ars

Fotografie: Ivor Grattan-Guinness 1989, in: Joseph W. Dauben/ Niccolò Guicciardini/ Albert Lewis/ Karn Hunger Parshall/ Adrian C. Rice, “Ivor Grattan-Guinness (June 23, 1941–December 12, 1914)”, Historia Mathematica 42 (2015) - Peckhaus, Volker
Pages 385–406, 396

Arno Schmidts ‚Ort‘ innerhalb der Nachkriegsliteratur - Eke, Norbert Otto (Arno Schmidt und der Kanon)

Der Witz als ästhetische Entautomatisierung. Shoah und Lachen - Eke, Norbert Otto (Der jüdische Witz. Zur unabgegoltenen Problematik einer alten Kategorie)

„Das Eigentliche ist das Unsagbare“. Angela Krauß‘ Poetik der Aussparung - Eke, Norbert Otto (Text + Kritik X/15)

Aus dem Labyrinth finden. Jüdisches Gedächtnis - Eke, Norbert Otto (Wendejahr 1995. Transformationen der deutschsprachigen Literatur)

„O wüsstet ihr, wie sehr mich das Gewissen beisset“. Zur Moralität politischen Handelns im Trauerspiel des frühen 18. Jahrhunderts - Eke, Norbert Otto (Gewissen. Interdisziplinäre Perspektiven auf das 18. Jahrhundert)

Gebrauchte Juden, oder: „Es müßte doch für einen Juden möglich sein, nicht Jude zu sein.“ - Eke, Norbert Otto (Heimat – Identität – Mobilität in der zeitgenössischen jüdischen Literatur)

Zeit aus den Fugen. Konstruktionen der Wende - Eke, Norbert Otto (Études Germaniques 70, Nr. 2: Écritures du Wenderoman)

Gottfried Benns „Todessprung aus der Enttäuschung in den Faschismus“. Ein paradigmatischer Fall? - Eke, Norbert Otto (Benn Forum Band 4 2014/15. Beiträge zur literarischen Moderne [Jahrbuch])